Double cross : Japanese Americans in Black and white Chicago - Harden, Jacalyn D. (University of Minnesota Press, 2003)
Jacalyn D. Harden examines the Japanese American community of Chicagos Far North Side to form an innovative new framework for looking at race, identity, and political change. The result is a compelling and surprising account of racial interactions, one that clarifies the complex interweaving between black and Asian lives and reclaims a lost history of solidarity between the two groups.